Transcatheter Aortic Valve Implantation and Morbidity and Mortality-Related Factors: a 5-Year Experience in Brazil - Souza,André Luiz Silveira (2016)
Abstract Background: Transcatheter aortic valve implantation has become an option for high-surgical-risk patients with aortic valve disease. Objective: To evaluate the in-hospital and one-year follow-up outcomes of transcatheter aortic valve implantation. Methods: Prospective cohort study of transcatheter aortic valve implantation cases from July 2009 to February 2015. Analysis of clinical and procedural variables, correlating them with in-hospital and one-year mortality. Results: A total of 136 patients with a mean age of 83 years (80-87) underwent heart valve implantation; of these, 49% were women, 131 (96.3%) had aortic stenosis, one (0.7%) had aortic regurgitation and four (2.9%) had prosthetic valve dysfunction. NYHA functional class was III or IV in 129 cases (94.8%). The baseline orifice area was 0.67 ± 0.17 cm2 and the mean left ventricular-aortic pressure gradient was 47.3±18.2 mmHg, with an STS score of 9.3% (4.8%-22.3%). The prostheses implanted were self-expanding in 97% of cases. Perioperative mortality was 1.5%; 30-day mortality, 5.9%; in-hospital mortality, 8.1%; and one-year mortality, 15.5%. Blood transfusion (relative risk of 54; p = 0.0003) and pulmonary arterial hypertension (relative risk of 5.3; p = 0.036) were predictive of in-hospital mortality. Peak C-reactive protein (relative risk of 1.8; p = 0.013) and blood transfusion (relative risk of 8.3; p = 0.0009) were predictive of 1-year mortality. At 30 days, 97% of patients were in NYHA functional class I/II; at one year, this figure reached 96%. Conclusion: Transcatheter aortic valve implantation was performed with a high success rate and low mortality. Blood transfusion was associated with higher in-hospital and one-year mortality. Peak C-reactive protein was associated with one-year mortality.